Enhanced photocatalytic activity of N, P, co-doped carbon quantum dots: An insight from experimental and computational approach. (October 2020) - Yashwanth, H.J.; Rondiya, Sachin R.; Dzade, Nelson Y.; Dhole, S.D.; Phase, D.M.; Hareesh, K.
Abstract: Herein, we demonstrate the single-step microwave radiation assisted approach to develop Nitrogen (N) and Phosphorous (P) co-doped carbon quantum dots (NP-CQD). The developed NP-CQD showed enhancement in visible light photocatalytic activity towards methylene blue dye degradation than that of N-CQD and P-CQD due to creation of energy states and reduced work function as estimated by Ultraviolet photoelectron spectroscopy and corroborated by first-principles Density Functional Theory (DFT) calculations. Highlights: N and P were co-doped to CQD by microwave radiation assisted method. NP-CQD showed enhancement in visible light photocatalytic activity. DFT calculations showed the decrease in work function of NP-CQD. P-CQD showed improved photocatalytic activity than N-CQD.